Pathological proliferation: a potential mechanism for poor CD4+ T cell recovery in people living with HIV - Zhang, Yang; Ji, Jiahao; Xie, Kaidi; Cai, Miaotian; Wang, Rui; Zhang, Xin; Chen, Xue; Zhang, Yulin; Wu, Hao; Wang, Wen; Li, Zhen; Zhang, Tong (Frontiers in Cellular and Infection Microbiology, 2024)
Background: People living with HIV (PLWH) fail to achieve normalization of CD4 + T cell counts and function, especially in immunological non-responders (INRs). The frequencies of Ki67 + CD4 + T cells were inversely associated with CD4 + T cell counts in HIV infected patients. Early ART did not normalize CD4 + T cell proliferation. However, the features of the abnormal proliferation CD4 + T cell in INRs are far from known.Method: PLWH were divided into INRs (n= 16) and immunological responders (IRs, n= 53) groups.technique was used to measure plasma levels of cytokines and chemokines. Correlation analyses were conducted to evaluate associations between the degree of CD4 + T cell proliferation and immune function.The percentage of Ki67 + CD4 + T cells were significant higher in INRs, and we defined these cells with significant higher level of Ki67, as over-proliferating cells. No significant difference of markers' expression (HLA-DR, CD38, CD57, PD-1, PD-L1, CD107a, perforin) was found between INRs and IRs. Compared with naïve CD4 + T cells in INRs, Ki67 + CD4 + T cells exhibited lower levels of CD57 and CD38. Whereas Ki67 + T cells exhibited higher levels of CD38 and CD57 and activation compared with differentiated mature central memory CD4 + T cells and effector memory CD4 + T cells . Ki67 + cells did not show higher levels of senescence and activation compared to certain Ki67 -CD4 + central memory T cells in IRs. Furthermore, Ki67 + CD4 + Tcm cells exhibited positive correlations with pro-inflammatory cytokines.We proposed and validated the hypothesis of "pathological proliferation" in INRs: excessive proliferation of CD4 + T cells in INRs may be accompanied by aberrant activation, senescence and loss of immune function. Eventually, such over-proliferating but poor-quality cells in INRs result in incomplete recovery of both CD4 + T cell counts and function. An intervention that enhancing the proliferative capacity or functional ability or both of CD4 + T cell in INRs might therefore be beneficial.